Pengaruh Pendidikan Akuntansi Syariah terhadap Perilaku Etis Mahasiswa - Nanik Sri Utaminingsih (Jurnal Ilmiah Aset, 2008)
The objective of the research is to find out empirical evidence of the influence and te different between Syariah Acoounting Education and etical Behavior at student in University. The population of this study is from student at UNNES, UNDIP and UNISULA, UNIMUS. Sample collected used questioner to ask them about religiusitas and ethical behavior. Amount of this sample is 101 student from university. Before test of hypothesis, researcher tested of quality data reliability test, validity test and Kolmogorov-Smirnov test. After this, the test of hypothesis used Spearman Correlation and Mann Whitney U-Test because the data was not normal and the result of this research showed that strong correlation between Syariah Education to Ethical Behavior. The research found the empirical evidence about the Different Religiusitas Indeks and the different Ethical Behavior between student at Syariah based University and Non-Syariah based University. Based on the test, the conclusions are Syariah Accounting Education can influenceethical it find the Different Religusitas Indeks and the different Ethical Behavior between student at Syariah based University and Non-Syariah based University.